Inspiration divine : Lady Hamilton en sibylle par Élisabeth Vigée-Le Brun - Contogouris, Ersy (RACAR : Revue d'art canadienne / Canadian Art Review, 2010)
Élisabeth Vigée-Le Brun designated her portrait of Lady Hamilton as a Sibyl (1791–92) as one of her favourite works. Despite this, "her" Sibyl, as she simply and affectionately called it in her Souvenirs, remains little studied by art historians. This painting is heavily permeated by the tensions that seem to have existed between Vigée-Le Brun and Hamilton. It displays a number of departures from the conventions and expectations regarding portraiture, to such an extent that the artist seems to have tried to empty the canvas of her sitter’s presence. Grounded in Vigée-Le Brun’s own writings and a detailed reading of the painting, this paper contends that Lady Hamilton as a Sibyl should be understood within a wider discussion on the nature of genius. It argues that this painting can be read as a statement on feminine genius at the very moment the notion of genius began to acquire its modern meaning. Vigée-Le Brun displaced Hamilton from the work in order to project herself into it, in a process of identification with the sibyl and affirmation of her own creative genius.